Analisis Kesulitan Menulis Karangan Narasi pada Siswa Kelas IV SDN Peterongan Semarang - Mellisa Putri Adeliana; Mudzanatun Mudzanatun; Aries Tika Damayani (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2026)
This qualitative descriptive study analyzes the difficulties fourth-grade students at Peterongan Elementary School, Semarang, have in writing narrative essays and the contributing factors. The research method employed a qualitative descriptive approach with 23 fourth-grade students and their teachers. Data were collected through observation, writing tests, interviews, and documentation validated through triangulation and data analysis. The results indicate that students' primary difficulties are identifying the main idea (the story lacks focus), developing a less coherent plot, and using spelling, punctuation, and capitalization. Contributing factors include monotonous learning methods, low reading literacy, limited cognitive development, and poor concentration.